2008
DOI: 10.1007/s10495-008-0284-8
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic induced apoptosis in malignant melanoma cells is enhanced by menadione through ROS generation, p38 signaling and p53 activation

Abstract: This study thus provides an insight into innovative mechanisms of melanoma sensitization, a proper cure against which is still elusive. Taken together, our data also provides the first evidence of arsenic activity accentuation by menadione through modulation of specific signaling-pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 50 publications
(72 reference statements)
1
52
0
Order By: Relevance
“…85 Recent studies have suggested that p53 plays a critical role in the cellular response to DNA damage and apoptosis induced by ROS. 86,87 Our Western blotting data ( Figure 10) suggest that both B-AgNPs and F-AgNPs activated p53, which mediated apoptosis. This result is consistent with previous studies by Lu et al and Mroz et al, which showed that nanoparticles and ROS can induce DNA damage, activate p53, and mimic irradiation-related carcinogenesis pathways.…”
mentioning
confidence: 86%
“…85 Recent studies have suggested that p53 plays a critical role in the cellular response to DNA damage and apoptosis induced by ROS. 86,87 Our Western blotting data ( Figure 10) suggest that both B-AgNPs and F-AgNPs activated p53, which mediated apoptosis. This result is consistent with previous studies by Lu et al and Mroz et al, which showed that nanoparticles and ROS can induce DNA damage, activate p53, and mimic irradiation-related carcinogenesis pathways.…”
mentioning
confidence: 86%
“…Under normal circumstances, its production and resolution are in dynamic balance, and the redox state of the intracellular environment maintains a stable state. A great deal of research indicated that many antitumor drugs are closely related to the ROS initiation within tumor cells [19][20][21]. Such as antitumor drug arsenic trioxide (As 2 O 3 ), polysaccharides, quinone anticancer drugs, and so on, they can produce a lot of ROS inducing tumor cell apoptosis [22].…”
Section: Discussionmentioning
confidence: 99%
“…These findings revealed that cell viability in response to arsenite is regulated by stimulation of GSH synthesis in GCs, and that BSO abolished arsenic-mediated progesterone production may be due to cell apoptosis. In many cases, arsenite increases ROS generation and facilitates the major apoptotic signaling events (Chowdhury et al, 2010). Ghibelli et al (1998) reported that GSH played an anti-apoptotic role in apoptogenic treatment cells.…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%